OPTIMALISASI KOMUNIKASI INTERNAL KANTOR KELURAHAN SIDOREJO HILIR: STUDI KASUS MINIMNYA INTERAKSI LANGSUNG ANTARA LURAH & PEGAWAI - Sihombing, Angel; Rajagukguk, Asya; Limbong, Sabar; Saragih, Yosheline (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
This research discusses internal communication in Sidorejo Hilir Urban Village Office that has not been running optimally, especially related to the lack of direct interaction between the head of village and employees. The purpose of this research is to find out the causes of ineffective communication, its impact on employee performance, and optimization strategies that can be applied. The method used is descriptive qualitative with a case study approach, through observation, interview, and documentation techniques. The results showed that the communication pattern formed was still one-way and centered on the head of the village secretary, so that employees felt uninvolved in the work process. The discussion shows that this condition is reinforced by a rigid bureaucratic structure, psychological barriers, and a less participatory leadership style. The conclusion of this study is that ineffective internal communication has an impact on low work motivation, weak coordination, and less than optimal public services. Therefore, it is recommended to increase the frequency of direct interaction, create a culture of two-way communication, and provide communication training to leaders and employees.